EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING BERBANTUAN LKS TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA MATERI SEGIEMPAT KELAS VII SMP 5 SRAGI - Widiyaningsih, Rita; Supardi, Supardi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
This research is experimental research that aims to find out the information about the effectiveness of the Snowball Throwing type of Cooperative model of Teaching and Learning using LKS’s help towards quadrangle material, marked: (1) if the problem solving method using Snowball Throwing teaching and learning model using the LKS’s help can help the students to achieve the KKM (standard of minimum score), (2) if the problem solving skill of the experimental class is better than the control class’, and (3) the influence of achievement motivation using Snowball Throwing teaching and learning model with the LKS’ help towards problem solving skill. The population in this research is all 7th Graders of SMP N 5 Sragi, which consist of 5 classes. With the simple random sampling technique, 2 classes are chosen: VII A as the experimental class and VII B as the control class. The research variables are: achievement motivation using Snowball Throwing teaching and learning model with the LKS’ help as free variables (X) and the problem solving skill as a bound variable (Y). In order to gather the data, method of questionnaire and test are used. The results of the research show: (1) thitung (count) = 4,5049 > ttabel (table) = 2,0301 it means that the problem solving method using Snowball Throwing teaching and learning model using the LKS’s help can help the students to achieve the KKM (standard of minimum score), (2) thitung (count) = 4,6211 > ttabel (table) = 1,995 it means that the problem solving skill of the experimental class is better than the control class’, and (3) there is a positive influence of the motivation of achievement using Snowball Throwing teaching and learning model with the LKS’ help towards problem solving skill about 63,12%. Based on those three results of the research, it can be concluded that the Snowball Throwing teaching and learning model using the LKS’s help is effective towards the students’ problem solving skill.